ON THE SOLUTION OF 3D FRICTIONAL CONTACT PROBLEMS WITH BOUNDARY ELEMENT METHOD AND DISCONTINUOUS ELEMENTS USING A GENERALIZED NEWTON METHOD WITH LINE SEARCH (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
This paper presents the implementation of an algorithm for the solution of 3D elastic contact problems with friction using the Boundary Element Method (BEM) with discontinuous elements. A standard BEM implementation is used, and the coupling of the potential contact zone is imposed through a projection function which treats each region independently, and is updated along with the changes to the contact state. The contact restrictions are fulfilled through the augmented Lagrangian, and the solution is found using the Generalized Newton Method with line search. With this method is possible to avoid the calculation of the non-linear derivatives, allowing for a fast solution of the problem. A classic contact problem is solved to evaluate the accuracy of the method and to provide a comparison with analytic solution.